Data book for electronic technicians and engineers - Lenk, John D. (Prentice-Hall, 1968)
There is no scarcity of data on the subject of electronics. There are hundreds of books filled to the brim with basic theory and equa-tions. But this great variety, in itself, creates a problem. Where and how do you pin down specific information of a particular phase of electronics?